Burden of childhood and adolescence asthma in Nigeria: Disability adjusted life years. (March 2022) - Ughasoro, Maduka D.; Eze, Joy N.; Oguonu, Tagbo; Onwujekwe, Emmanuel Obinna
Abstract: Background: A better representation of the burden of childhood asthma should rely on both morbidity and mortality and not only mortality. This will reduce the dearth of information on burden of childhood asthma, and enhance evidence-based decision-making. In this study, burden of childhood asthma was estimated, using disability-adjusted-life-years (DALYs), factoring in the disability weights for asthma, age at mortality and life expectancy. Methods: The study was conducted at the University of Nigeria Teaching Hospital, Enugu. An Interviewer Administered Questionnaire was used to collect information from parents of children with asthma who presented to respiratory clinics regarding level of their asthma control (controlled, partially controlled and poorly controlled asthma), their age distributions, and gender. The prevalence of asthma, prevalence of associated disability, and case-fatality were obtained from previous publications. The DALYs were estimated by adding together the years lost to disability (YLDs) and years lost to life (YLLs) to asthma (DALYs = YLD + YLL). DALYs were dis-aggregated by age group and by whether their asthma were controlled, partially controlled and poorly controlled. Results: A total of 66 children with asthma were studied. The proportion of the subjects with controlled, partially controlled and poorly controlled asthma were 26 (39.4%), 31 (47%), and 9 (13.6%) respectively. The subjects that had some form of asthma-related disability were 16 (24.3%). Childhood asthma caused 23.6–34.24 YLLs per 1000 population, 0.01–1.28 YLDs per 1000 population and 24.23–34.41 DALY per 1000 population. There was minimal difference in DALYs across the three clinical categories, but this was consistently higher among older children 12–17 years. The estimated national DALYs was 407820.2, reflecting about of 1.6% of the global all age (children and adults) DALYs of 24.8 million. Conclusion: The DALYs due to childhood asthma were high and did not vary much across the clinical categories, but increased with age. This imperatively necessitates the de-emphasis on just clinical responses as an indicator of the efficiency of childhood asthma control interventions but rather a holistic approach should be adopted considering the limitations the child suffers as a component of both life and environmental modification in a deliberate attempt to prevent attacks. The ability of the child to function optimally while on treatment should be considered in the treatment impact review.